Efektivitas pembelajaran ilmu resep di SMK bidang keahlian farmasi di Kabupaten Cilacap - Hendri Hermawan (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2013)
Penelitian ini bertujuan untuk mengetahui: (1) Efektivitas pembelajaran ilmu resep di SMK bidang keahlian farmasi di Kabupaten Cilacap, dan (2) Pengaruh kompetensi profesional guru, pengelolaan kelas dan sarana prasarana pembelajaran dengan efektivitas pembelajaran ilmu resep pada siswa SMK bidang keahlian farmasi di Kabupaten Cilacap. Populasi seluruh siswa SMK bidang keahlian farmasi kelas XI di kabupaten Cilacap. Pengumpulan data menggunakan angket dengan model skala likert dan rating scale. Teknik analisis data yang digunakan adalah analisis deskriptif, analisis regresi sederhana dan analisis regresi ganda pada taraf signifikansi 5%. Hasil analisis deskriptif menunjukkan bahwa efektifitas pembelajaran ilmu resep di SMK bidang keahlian farmasi di Kabupaten Cilacap berada pada kategori sangat baik. Hasil analisis regresi ganda menunjukkan bahwa terdapat pengaruh yang positif secara bersama-sama kompetensi profesional guru, pengelolaan kelas dan sarana prasarana pembelajaran terhadap efektivitas pembelajaran ilmu resep di SMK bidang keahlian farmasi di Kabupaten Cilacap dengan koefisien korelasi 0,521 dengan Fhitung=15,497 dan sumbangan efektif 27,1%. THE EFFECTIVENESS OF PRESCRIBING SCIENCE LEARNING AT PHARMACY SKILL PROGRAM OF VOCATIONAL HIGH SCHOOL IN CILACAP REGENCYAbstractThis study aims to reveal: (1) the effectiveness of prescribing science learning at pharmacy skill program of vocational high school in Cilacap Regency, and (2) the effect of teacher's professional competency, class management and educational facilities and infrastructures on the effectiveness of prescribing science learning at pharmacy skill program of vocational high school in Cilacap Regency. The population is all grade XI students of the pharmacy skill program of vocational high schools in Cilacap Regency. The data were collected by means of questionnaires with the Likertscale model and rating scale. The data were analyzed using the descriptive, simple regression, and multiple regression analysis at a significance level of 5%. The results of the descriptive analysis show that the effectiveness of perscribing science learning at pharmacy skill program of vocational high school in Cilacap Regency is in the very good category. The result of the multiple regression analysis shows that there is a positive and significant effect of the teacher's professional competency, class management and educational facilities and infrastructures as an aggregate on the effectiveness of prescribing science learning at pharmacy skill program of vocational high school in Cilacap Regency with a correlation coefficient of 0.521 with Fobserved= 15.497 and an effective contribution of 27.1%.